Baltų priesaga -ingas ir germanų -ing - Ambrazas, Saulius (Baltistica, 1994)
BALTIC SUFFIX -ingas AND GERMANIC SUFFIX -ing The formation of Baltic adjectives with the suffix -ingas is very similar to that of Germanic nomina attributiva by means of the suffix -ing (cf. Lith. vargìngas, Latv. vãrdzîgs „miserable, poor, hard, difficult” and OHG. arming „poor person”). Proper, place, names and hydronims with -ing-, -ang-, -eng-, -ung- especially in Old Prussian, Curonian, Yotvingian as well as the existance of the related suffixes -inas (cf. OLith. kruvingas and Lith. krùvinas, OCS. krъvъnъ „bloody”), -ind- (cf. jotvingiai „West Baltic tribe” < „who live in Jotva” abd galindai „the other West Baltic tribe” < „who live in the end”, Lith. galìnis „final, last”) in the Baltic languages testify the ancient character of the Baltic suffix -ingas. The rareness of the derivatives with -ing in Gothic and some other old Germanic texts and the consonant g (instead of k: the Indo-European determinative *-g- corresponds to Germanic -k-) in the Germanic suffix -ing enable us to suppose the suffix -ing to be borrowed from the West Baltic languages. This hypotheses supported by two other derivative inovations in Baltic and Germanic: nomina qualitatis with the suffixes *-ō-men- (cf. Lith. mažúomenė „childhood; young people” and mažmẽnė „childhood; small things”, Goth. dat. sing. aldōmin „for old age”) and *-isko- (cf. deiwūstisku (Seligkeyt) III 7522, OLith. bernìškė „childhood” and OSkand. bernska „childhood”).